Influence of biological and social-historical variables on the time taken to describe an angiosperm. - Cavallin, E; Munhoz, C; Harris, S; Villarroel, D; Proença, C (American Journal of Botany, 2016)
Premise of the Study By convention, scientific naming of angiosperm species began in 1753; it is estimated that 10–20% of species remain undescribed. To complete this task before rare, undescribed species go extinct, a better understanding of the description process is needed. The South American Cerrado biodiversity hotspot was considered a suitable model due to a high diversity of plants, habitats, and social history of species description. Methods A randomized sample of 214 species (2% of the angiosperm fl ora) and 22 variables were analyzed using multivariate analyses and analysis of variance. Key Results Plants with wide global distributions, recorded from many areas, and above 2.6 m were described significantly earlier than narrowly distributed, uncommon species of smaller stature. The beginning of the career of the botanist who first collected the species was highly significant, with an average delay between first collection and description of 29 yr, and between type collection and description 19 yr; standard deviations were high and rose over time. Over a third of first collections were not cited in descriptions. Trends such as scientific specialization and decline of undescribed species were highlighted. Descriptions that involved potential collaboration between collectors and authors were significantly slower than those that did not. Conclusions Results support four recommendations to hasten discovery of new species: (1) preferential collecting of plants below 2.6 m, at least in the Cerrado; (2) access to undetermined material in herbaria; (3) fieldwork in areas where narrow-endemic species occur; (4) fieldwork by knowledgeable botanists followed by descriptive activity by the same.